Natural durability, preservative treatability and protection of several hardwoods of Sarawak - Ling, Wang Choon (Universiti Malaysia Sarawak (UNIMAS), 2013)
Before 1977, there were no studies on natural durability and treatability of Sarawak timbers. Most information on durability was anecdotal, the species then assumed to be very durable were Belian, Selangan batu, Penyau, Kapur, Resak and Bakau. Timber Research and Technical Training Centre therefore established a graveyard test site for such field studies so that useful data on utilization of Sarawak timbers could benefit the Sarawak forest products industry. The objectives of this thesis are to determine from 30 years of research on natural (in-ground) durability (of mainly the outer heartwood present in a majority of wood species studied) and preservative treatability the relative natural durability and degree of protection of some preservative treated Sarawak timbers. The durability of 26 refractory and 106 nonrefractory timber species with and without preservative treatments was established by regular assessment of stakes in ground contact at the Sarawak Tree Improvement Centre located at Oya Road, Sibu, adopting the ASTM D1758 for assessing replicated stakes of the wood species [stake replication, 20; stake size: 19 x 19 x 457 (long.) mm]. To ensure uniform and good decay condition, plots were alternated between areas with original vegetation cover and a permanent vegetation belt was maintained around each row of stakes. Stake specimens planted over the years 1977-2000 were each visually rated at 6-month intervals for the first 10 years from installation and subsequently once a year until April 2008. The field results were analyzed using SPSS Windows Version 15.0. Comparative natural durability ratings between the 133 wood species, matched against wood density groups, commercial timber groups (e.g. the keruings, mixed light hardwoods, the merantis, the kapurs) and refractory-versuspermeable groups, revealed statistically that the very durable species are Eusideroxylon zwageri, Shorea pluricostata, Upuna borneensis and Gymnostoma nobile. The 16 durable species included Shorea exelliptica, Shorea flava, Shorea laevis, Pentace corneri, Shorea acuminatissima, Tectona grandis, Palaquium rivulare, Hopea latifolia, Hopea beccariana and Shorea uliginosa. The 39 moderate durable species included Tristania whiteana, Cantleya corniculata, Jackia ornata, Parashorea smythiesii, Dialium indum, Dacrydium elatum, Anisophyllea beccariana, Shorea carapae, Lithocarpus cantleyanus, Pometia pinnata and Anisoptera grossivenia. The remaining 74 species, including potential plantation species such as Acacia mangium, Neolamarckia cadamba, Shorea macrophylla, Dyera polyphylla and Octomeles sumatrana, were found to be non-durable. Statistically, it was shown that wood species with high Chromated Copper Arsenate (CCA) retentions with mean retention values <20 kg/m3 were in good condition after 20 years in ground contact while a majority of Chromated Copper Borate (CCB) treated timbers at a mean retention <24 kg/m3 lasted just 10 years. Creosote treated timbers (mean retention 108 kg/m3) failed by the 13th year while Fluor-Chrome-Arsenate-Phenol (FCAP, mean retention 21 kg/m3) failed by the 8th year. From statistical analysis of OHW, natural durability of 133 timber species as well as durability of 131 timbers treated with these wood preservatives was found to vary considerably. Overall, it was found that 26 species (19.5% of all species tested) were refractory treated using CCA full-cell treatment while 107 species (80.5%) were nonrefractory. The 26 refractory species consisted of four very durable (3% of all species), seven durable (5.2%) and 15 moderately durable (11.3%) species. None of the refractory species belonged to the non-durable group. The non-refractory group had 74 species (55.6% of all species) belonging to non-durable group, 24 species (18.1% of all species) belonging to moderately durable and nine species (6.8%) belonging to durable group. None of the nonrefractory species belonged to the very durable grouping. From these overall findings the timber utilization prospects and issues of untreated and treated Sarawak species are discussed in relation to matters such as: similar work around the world, test methodology issues, wood used in agriculture, construction and wood composites, their wood density classes, trends between botanical groups of species, future plantations, and future research needs beneficial to the Malaysian and Sarawak forest products industry are proposed.